Methodological Approaches to the Integrated Evaluation of Brand Strength Based on the System of Indicators and Modeling of Generalized Results of the Consumer Survey - O. A. Shikhova (Статистика и экономика)
The article presents in detail the methodological approaches to calculating the integrated assessment of brand strength, as well as the results of testing the system of indicators and the mathematical model on the example of a comprehensive assessment of the power of the regional brand “The real Vologda product”. The developed methodology as a whole is the result of research within the framework of the implementation of a state scientific grant from the government of the Vologda Oblast. In addition to the system of indicators, built on the basis of the results of generalization of theoretical materials and practical experience of domestic and foreign authors on this problem and the use of modeling techniques, a questionnaire for researching consumer attitudes towards brand product is presented, a methodology for presenting the results of respondents’ answers to questions in a quantitative coefficient form is described. A mathematical model has been developed to calculate the integrated indicator for assessing brand strength based on the survey results, which includes information received both from the consumer and from outside experts. The scaling of the possible values of this estimate has been performed. The matrix of indicators for assessing brand strength is graphically presented, which allows you to give both a general and a detailed qualitative characteristic of brand strength based on the results of using the model, to determine the strengths and weaknesses of the brand, and to reveal its potential. Purpose of the research. The purpose of this research was to develop a comprehensive methodology for assessing brand strength and its approbation on the example of the regional product brand “The real Vologda product”. Materials and methods. The research was carried out on the basis of data from a questionnaire survey of consumers and experts, construction of a mathematical model, including coefficient values of indicators reflecting the level of indicators that allow assessing brand strength in the complex. Mathematical and statistical methods were used as the basis for transferring the results of the respondents’ answers into the coefficient form, their standardization and generalization. A graphical method was used to represent the matrix of indicators for assessing brand strength. Results. The studied domestic and foreign methods for assessing the power of a brand, with all their obvious positive aspects and completeness, have a weak side – they are qualitative from the standpoint of characteristics of the strength, potential and status of a brand, they only allow a description of these properties. As a result of the study, it was possible to generalize the existing experience, develop a system of brand strength indicators, draw up a questionnaire for a consumer survey that allows collecting information to measure the values of these indicators, build a mathematical model for calculating an integrated brand strength assessment, develop a methodology for the qualitative characteristics of the results of calculating this assessment based on the matrix. Approbation of the methodology made it possible to obtain a comprehensive quantitative assessment of the power of the regional product brand “The Real Vologda product”, to formulate recommendations that were taken into account by the copyright holder of the brand – Budgetary Institution of the Vologda Region “Vologda Information and Consulting Center of the Agro-Industrial Complex” when elaborating its development strategy. Conclusion. The results of assessing the influence of the indicators’ contribution to the integrated indicator of the brand strength “The Real Vologda product” showed that its strength and potential are mostly due to the factors such as physical availability and quality of products, highly rated by consumers, as well as demand from the buyer. At the same time, according to the experts, these factors also received very high weighted coefficients.